MySmartSolution Platform – a conceptual solution in enhancing the societal wellbeing through smart-based technology services - Ahmad Dahlan, Abdul Rahman; Md. Zulkifli, Muhammad Faizal; Talib, Ammar; Wan Juhari, Wan Muhammad Firdaus; Azizan, Muhammad Syazwan (Eclat Research Publication, 2015)
The population of Muslims globally is estimated to be more than 1.6 billion, which represents about one-fifth of the world’s population. The recent religious awakening of Muslims and their realization of the importance of compliance with Shari’ah laws in business dealings have enabled them to achieve their economic and wellbeing goals. This conceptual paper proposed a business, which is providing IT products and services throughout Malaysia. This concept has potential to become the biggest solution provider in the country as IT products and smart devices are needed today. Literature reviews, nine (9) blocks of Business Model Canvas (BMC), Value Proposition Design (VPD), and Environmental Map framework are used methodology for this paper. As the extent, this concept also serves the customers with cheaper price compared to other competitors but high quality product and have warranty for each items. Besides, our company also have charity program. On the initial plan, We will provide tools like LCD and projector to specified mosque in order for jamaah to get knowledge through video presentation. Besides, the tools provided also can be used when there are crowded people attend to hear any talks organized by the mosque. Other than that, special discount will be given for needy students to purchase our product. Some criteria has been choose in order to identify them. Thus, demonstrating the contribution of our company in realizing partly the meaning of “Rahmatan lil Alamin”.